Complications in lumbar spine surgery: A retrospective analysis - Proietti, Luca (Medknow Publications & Media Pvt Ltd, 2013)
BACKGROUND: Surgical treatment of adult lumbar spinal disorders is associated with a substantial risk of intraoperative and perioperative complications. There is no clearly defined medical literature on complication in lumbar spine surgery. Purpose of the study is to retrospectively evaluate intraoperative and perioperative complications who underwent various lumbar surgical procedures and to study the possible predisposing role of advanced age in increasing this rate. MATERIALS AND METHODS: From 2007 to 2011 the number and type of complications were recorded and both univariate, (considering the patients’ age) and a multivariate statistical analysis was conducted in order to establish a possible predisposing role. 133 were lumbar disc hernia treated with microdiscetomy, 88 were lumbar stenosis, treated in 36 cases with only decompression, 52 with decompression and instrumentation with a maximum of 2 levels. 26 patients showed a lumbar fracture treated with percutaneous or open screw fixation. 12 showed a scoliotic or kyphotic deformity treated with decompression, fusion and osteotomies with a maximum of 7.3 levels of fusion (range 5-14). 70 were spondylolisthesis treated with 1 or more level of fusion. In 34 cases a fusion till S1 was performed. RESULTS: Of the 338 patients who underwent surgery, 55 showed one or more complications. Type of surgical treatment (P = 0.004), open surgical approach (open P = 0.001) and operative time (P = 0.001) increased the relative risk (RR) of complication occurrence of 2.3, 3.8 and 5.1 respectively. Major complications are more often seen in complex surgical treatment for severe deformities, in revision surgery and in anterior approaches with an occurrence of 58.3%. Age greater than 65 years, despite an increased RR of perioperative complications (1.5), does not represent a predisposing risk factor to complications (P = 0.006). CONCLUSION: Surgical decision-making and exclusion of patients is not justified only by due to age. A systematic preoperative evaluation should always be performed in order to stratify risks and to guide decision-making for obtaining the best possible clinical results at lower risk, even for elderly patients.